Single-case and small-n experimental designs : a practical guide to randomization tests - Dugard, Pat.; File, Portia; Todman, John B.; Todman, John B. (New York, NY : Routledge, 2012)
'Randomization tests are not a new idea, but they only became really useful after the advent of fast computing. Making randomization tests accessible to many more potential users by providing the means to use them within familiar statistical software, this book serves as an introduction and provides macros to perform in the familiar environments of SPSS and Excel. Though we expect that the book will still appeal to researchers, we believe the changes in the new edition will make the book an essential aid for graduate and senior undergraduate courses in statistics, data analysis, and/or research methods, taught in departments of psychology (especially clinical or counseling psychology), medicine, nursing, and other health and social sciences'--
Rev. ed. of : Single-case and small-n experimental designs / John B. Todman, Pat Dugard, 2001.
Includes bibliographical references and index.
Keywords: Statistical hypothesis testing; Experimental design